2018
DOI: 10.1016/j.stem.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

AMPK/FIS1-Mediated Mitophagy Is Required for Self-Renewal of Human AML Stem Cells

Abstract: Leukemia stem cells (LSCs) are thought to drive the genesis of acute myeloid leukemia (AML) as well as relapse following chemotherapy. Because of their unique biology, developing effective methods to eradicate LSCs has been a significant challenge. In the present study, we demonstrate that intrinsic overexpression of the mitochondrial dynamics regulator FIS1 mediates mitophagy activity that is essential for primitive AML cells. Depletion of FIS1 attenuates mitophagy and leads to inactivation of GSK3, myeloid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
197
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 66 publications
(81 reference statements)
7
197
0
Order By: Relevance
“…Several studies have revealed that AMPK activation can result in mitochondrial fission that in turn induces mitochondrial dysfunction (Gowans, Hawley, Ross, & Hardie, 2013;Zheng et al, 2018). AMPK regulates Fis1 expression in human acute myeloid leukemia stem cells and inhibition of AMPK reduces the level of Fis1 (Pei et al, 2018). On the contrary, AMPK F I G U R E 5 Migration inhibitory factor (MIF)-bone marrow (BM)-mesenchymal stem cell (MSC)-exosomes (exo) treatment improves heart function and ameliorates fibrosis after myocardial infarction (MI).…”
Section: F I G U R Ementioning
confidence: 99%
“…Several studies have revealed that AMPK activation can result in mitochondrial fission that in turn induces mitochondrial dysfunction (Gowans, Hawley, Ross, & Hardie, 2013;Zheng et al, 2018). AMPK regulates Fis1 expression in human acute myeloid leukemia stem cells and inhibition of AMPK reduces the level of Fis1 (Pei et al, 2018). On the contrary, AMPK F I G U R E 5 Migration inhibitory factor (MIF)-bone marrow (BM)-mesenchymal stem cell (MSC)-exosomes (exo) treatment improves heart function and ameliorates fibrosis after myocardial infarction (MI).…”
Section: F I G U R Ementioning
confidence: 99%
“…If NRF2 proves to be upregulated in LSCs, this could potentially be the reason of the higher mitochondrial content and respiration in LSCs compared to their normal counterparts. Interestingly, two studies have recently uncovered different mechanisms for mitophagy in AML LSCs and HSCs , suggesting that this process might be regulated in a context‐dependent manner. Although future studies will help elucidating these puzzling mechanisms in different cell types, it is now clear that CML and AML LSCs share a common dependency on OXPHOS, which may be a therapeutically exploitable vulnerability.…”
Section: Interplay Between Autophagy and Oxidative Stress In Lscsmentioning
confidence: 99%
“…Interestingly, when comparing residual healthy CD34+ cells with CD34+ cells that acquired the preleukemic SRSF2 mutation, the FIS1 gene was most significantly upregulated in the mutant cells. FIS1 activation has previously been shown to be critical for the transformation of healthy HSCs to LSCs (Pei et al , 2018) (Figure 5c). The subsequently acquired leukemic CEBPA mutation caused expression changes in several genes (Figure 5d).…”
Section: Resultsmentioning
confidence: 84%
“…In the AML patient studied here, we have found that initial pre-leukemic SRSF2, TET2 and SPEN mutations resulted in the clonal expansion of developmentally immature cells with skewed lineage priming but a high net contribution to all blood and immune lineages except T cells. On a molecular level, the transition from healthy to pre-leukemic CD34+ cells was accompanied by increased expression of FIS1 , a process that has recently been characterized as crucial for LSC maintenance (Pei et al , 2018). Clonal evolution subsequently resulted in the expansion of two subclones in addition to the remaining founder clone.…”
Section: Discussionmentioning
confidence: 99%